Moralitas, Kapabilitas, dan Perilaku Kerja Inovatif Aparatur Desa terhadap Pengelolaan Dana Desa - Amalia, Sri Wilujeng Rizki; Bhilawa, Loggar (E-Jurnal Akuntansi, 2023)
The research aims to determine the effect of morality, capability, and innovative work behavior on the management of village funds. The data collection method was carried out by distributing questionnaires to village officials who were directly related to village finances. The number of samples in the study were 178 people and were selected using a purposive sampling technique. The data analysis technique used in this study is multiple linear regression analysis using the IBM SPSS 26 application. The test results show that morality, capability, and innovative work behavior of village apparatus have a positive effect on village fund management. The morality, capability, and innovative work behavior of the village apparatus will be able to prevent village fund fraud and increase the accountability of village fund management. This research is expected to contribute to the implementation of good management of village funds in the reallocation and refocusing of the APBN. Keywords: Village Fund, Morality, Capability, Innovative Work Behavior, Village Fund Financial Management